Assessment of Involvement in a Peer Orientation Program - Poisson, Samantha E.; Russel, John H. (Canadian Journal of Counselling and Psychotherapy, 2011)
Evidence of the effectiveness of peer programs at the university level has not kept pace with the rapid growth of such programs. The present study compared an experimental group of 76, first years students who were trained as peer advisors with a control group of 34 similar characteristic peers on a variety of pre-post measures, including the University Experience Questionnaire (UEQ), the RosenbergSelf-Esteem Inventory (RSEI), and the Perceived Stress Scale. Results indicated no significant differences between the two groups, but exploratory analysis resulted in significant within group differences. Reasons for the results and implications for university first year peer programs are discussed.